PENGGUNAAN PENDEKATAN SAINTIFIK DAN MEDIA VIDEO UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA: The Use of Scientific Approach and Video Media to Improve Mathematics Learning Outcomes - Agung Riadin; Nilam Nilam (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2022)
This study aims to: (1) describe the activities of students and teachers using a scientific approach and video media for class IV B students at SDN 2 Menteng Palangka Raya in the 2021/2022 academic year. (2) Improving mathematics learning outcomes for grade IV B students at SDN 2 Menteng Palangka Raya in the 2021/2022 academic year, using a scientific approach and video media. The subjects of this study were students of class IV B SDN 2 Menteng Palangka Raya for the academic year 2021/2022, totaling 19 people. This type of research is Classroom Action Research (CAR). Data collection techniques used are observation and tests. The data analysis used is qualitative and quantitative analysis. The results of this study indicate that: (1) The activities of students and teachers when learning Mathematics in the material around the square and rectangle using a scientific approach and video media with very good criteria. (2) The mathematics learning outcomes of grade IV B students at SDN 2 Menteng for the academic year 2021/2022 have increased. Student learning outcomes in pre-action obtained an average value of 42.63 and student learning outcomes in cycle I obtained an average value of 64.73 with a classical completeness percentage of 57.89% and student learning outcomes in cycle II obtained an average score - an average of 81.57 with a classical completeness percentage of 94.73%.